High levels of pesticides found in illicit cannabis inflorescence compared to licensed samples in Canadian study using expanded 327 pesticides multiresidue method - Mathieu Gagnon; Tyler McRitchie; Kim Montsion; Josée Tully; Michel Blais; Neil Snider; David R. Blais (BMC, 2023)
Abstract Background As Cannabis was legalised in Canada for recreational use in 2018 with the implementation of the Cannabis Act, Regulations were put in place to ensure safety and consistency across the cannabis industry. This includes the requirement for licence holders to demonstrate that no unauthorized pesticides are used to treat cannabis or have contaminated it. In this study, we describe an expanded 327 multi-residue pesticide analysis in cannabis inflorescence to confirm if the implementation of the Cannabis Act is providing safer licensed products to Canadians in comparison to those of the illicit market. Methods An extensive multi-residue method was developed using a modified quick, easy, cheap, effective, rugged, and safe (QuEChERS) sample preparation method using a combination of gas chromatography-triple quadrupole mass spectrometry (GC-MS/MS) and liquid chromatography-triple quadrupole mass spectrometry (LC-MS/MS) for the simultaneous quantification of 327 pesticide active ingredients in cannabis inflorescence. Results Application of this method to Canadian licensed inflorescence samples revealed a 6% sample positivity rate with only two pesticide residues detected, myclobutanil, and dichlobenil, at the method's lowest calibrated level (LCL) of 0.01 μg/g. Canadian illicit cannabis inflorescence samples analysed showed a striking contrast with a 92% sample positivity rate covering 23 unique pesticide active ingredients with 3.7 different pesticides identified on average per sample. Chlorpyrifos, imidacloprid, and myclobutanil were measured in illicit samples at concentrations up to three orders of magnitude above the method LCL of 0.01 μg/g. Conclusion These results demonstrate the need of an extensive multiresidue method capable of analysing hundreds of pesticides simultaneously, to generate data for future policy and regulatory decision-making, and to enable Canadians to make safe cannabis choices.